2001
DOI: 10.1007/s002130100799
|View full text |Cite
|
Sign up to set email alerts
|

Neural circuit regulation of prepulse inhibition of startle in the rat: current knowledge and future challenges

Abstract: Our understanding of the neural regulation of PPI has increased tremendously over the past 15 years. Progress has come in "broad strokes", and a number of important details and complex questions remain to be addressed. It is anticipated that this is a "work in progress", and that the precise models for the neural regulation of PPI will evolve substantially in the coming years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
762
3
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 993 publications
(802 citation statements)
references
References 154 publications
28
762
3
9
Order By: Relevance
“…Even though most studies in the past have demonstrated the importance of the accumbens dopaminergic system (for a review see Swerdlow et al, 2001), our present findings clearly suggest a function of the accumbal GABAergic system in the regulation of PPI. Moreover, this regulatory function can almost certainly be attributed to the core rather than to the shell subregion.…”
Section: Effects Of Muscimol Infusion In the Core Or The Shell On Ppicontrasting
confidence: 49%
See 1 more Smart Citation
“…Even though most studies in the past have demonstrated the importance of the accumbens dopaminergic system (for a review see Swerdlow et al, 2001), our present findings clearly suggest a function of the accumbal GABAergic system in the regulation of PPI. Moreover, this regulatory function can almost certainly be attributed to the core rather than to the shell subregion.…”
Section: Effects Of Muscimol Infusion In the Core Or The Shell On Ppicontrasting
confidence: 49%
“…The nucleus accumbens appears to exert this regulatory role by virtue of its GABAergic output to the ventral pallidum and its projection to the pedunculopontine nucleus, providing a direct link to the primary startle circuit (Kretschmer and Koch, 1998). At the same time, it receives modulatory input via glutamatergic projections from 'limbic' structures (such as the hippocampus, medial prefrontal cortex, amygdala, and cingulate gyrus) and via dopaminergic projections from the ventral tegmental area (reviewed by Swerdlow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cocaine, but not amphetamine, elicited more expression of c-fos in the shell than in the core of nucleus accumbens . The nucleus accumbens is a key modulator of PPI (for review Swerdlow et al, 2001). The disruptive effects of amphetamine seem to correlate in time with DA increase in the nucleus accumbens in the rat .…”
Section: Discussionmentioning
confidence: 99%
“…PPI deficits are observed in psychotic disorders, such as schizophrenia, and are associated with dopamine (DA) dysregulation Swerdlow et al, 2001). PPI deficits are modeled in mice and rats following treatment with psychotomimetic drugs, such as d-amphetamine, cocaine, or phencyclidine .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the large number of studies on the neurotransmitter and neuroanatomical substrates of PPI Swerdlow et al, 2001), relatively little is known about the role of the norepinephrine (NE) system in regulating sensorimotor gating. This paucity is surprising, given the prominent role of NE in processes relevant to attention and cognitive functioning.…”
Section: Introductionmentioning
confidence: 99%